The management of hodgkin lymphomas in pregnancies. (5th October 2017) - Moshe, Yakir; Bentur, Ohad Shimshon; Lishner, Michael; Avivi, Irit
Abstract: Hodgkin lymphoma is the most common hematological malignancy in pregnancy. Its management presents several unique challenges, as decisions have to take both maternal and fetal risks into consideration. Using three hypothetical cases, we review current evidence and guidelines and suggest our recommendations for managing pregnant Hodgkin lymphoma patients. The opportunity for a prompt and accurate diagnosis should not be missed; this may be achieved by vigilance to suggestive symptoms, performance of biopsy which is not contraindicated during pregnancy and use of MRI for staging. Most patients should receive treatment with doxorubicin, bleomycin, vinblastine, dacarbazine (ABVD) after completion of the first trimester. Bridging therapy with corticosteroids or vinblastine should be considered during the first trimester. In most cases of early disease, the addition of chemotherapy cycles to the treatment plan seems preferable to radiation therapy. Diagnosis at relapse raises unique dilemmas regarding second‐line chemotherapeutic regimens and timing of consolidation with high‐dose therapy and autologous stem cell transplantation, an approach which is contraindicated during pregnancy. Considering the excellent outcomes of Hodgkin lymphoma outside pregnancy, every effort should be made to strive toward a curative treatment plan while balancing the multiple issues and dilemmas which arise when treating this malignancy in a pregnant patient.